2023
DOI: 10.1007/s11269-023-03424-0
|View full text |Cite
|
Sign up to set email alerts
|

Climatic and Other Global Changes as Current Challenges in Improving Water Systems Management: Lessons from the Case of Italy

Abstract: Climate change linked to human activities is affecting natural systems, increasing frequency and severity of water-related hazards. The issue of climate change pushes to tackle the expected risks in the water sector through a comprehensive and global view, with a revision of the paradigms considered as drivers of water resources development. Based on the evolution of these paradigms in Italy the main characteristics of an adaptive approach to climate change and other global changes are discussed relatively to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Weatherbit 12 provides an Agriculture Weather Forecast API, furnishing 8-day weather forecasts specifically tailored for the agriculture industry, thereby supporting informed decision-making by farmers. Rossi et al 13 employ a GIS-based geopedological approach to evaluate land suitability for chestnut groves, effectively demonstrating the role of GIS in promoting sustainable rural development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Weatherbit 12 provides an Agriculture Weather Forecast API, furnishing 8-day weather forecasts specifically tailored for the agriculture industry, thereby supporting informed decision-making by farmers. Rossi et al 13 employ a GIS-based geopedological approach to evaluate land suitability for chestnut groves, effectively demonstrating the role of GIS in promoting sustainable rural development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, it is believed that climate change closely connects to a region's water-related climatic system that directly determines its water security and vulnerabilities. Additionally, a previous study also identified a strong relationship between urban water stress risks and the water-energy-food (WEF) nexus [10]. Similarly, research has a long history of identifying the relationship between the effects of climate change on the water resources of the Colorado River basin [11].…”
Section: Introductionmentioning
confidence: 96%